Diseño del entrenamiento estandarizado para la línea de ensamblaje del modelo M4 GREAT WALL de la empresa Ciudad del Auto (CIAUTO) cantón Ambato provincia del Tungurahua. - Sandoval Maiza, Christian Vladimir (2018)
This project focuses on the Analysis and standardization; for the new personal training in the different process of production. With base to the information and study of the productive process that generate greater errors of product quality, the theoretical basis will be broken down of the standardized training; that help to consolidate the subsequent actions of the staff the methodology. The News personal training will be typified and it is going to design a valuation of the knowledge acquired through this standardized training. It brings a global analysis of the most critical stations of work for the new staff, achieving the highest levels of security, quality and production in the assemblage line achieving a continuous improvement. The training that is being used in the organization is susceptible to continuous improvement for this reason the final product satisfies the consumer needs, improving quality standards of the assembly line, this intended to help the organization since all operational staffs, it must have the same training and the same opportunities to increase their versatility and with this to ensure that absence is not crucial in the daily tasks to meet the quality and production required.